THE IMPACT OF GLOBALISATION ON LABOUR LEGISLATION RELATED TO EMPLOYEES IN ZIMBABWE - Fore, Cleopas; I. Ukpere, Wilfred (International Journal of Psychosocial Rehabilitation, 2021)
While there is widespread agreement that globalisation has affected developments across the globe and that it brought with it foreign direct investment and employment creation, there is no consensus on the nature and significance of its impact on labour legislation relating to employees. With specific reference to Zimbabwe, one view is that globalisation brought about employee rights. Another is that the advent of globalisation led to high liberalisation of the labour market through labour legislation deregulation to the disadvantage of employees. It is against this backdrop that the objective of this article is buttressed on the need to understand the impact of globalisation on labour legislation relating to employees in Zimbabwe. To achieve this objective, the study adopted a qualitative research approach based on the interpretivist research paradigm entrenched within a phenomenological research strategy. Being a qualitative study, the article relied on interviews and participants memoirs, which were thematically analysed. It was shown that globalisation has both a positive and negative impact on legislation relating to employees. The positives are provision of workplace democracy; employees’ rights; protection against unfair labour practices; and promulgation of anti-discrimination laws. The identified negatives included the increase of casual and temporal employment contracts; rising retrenchments; non-compliance with labour laws, particularly in the special economic zones (SEZ); use of cheap labour through outsourcing and labour brokering; and breach of minimum wages regulations. Findings showed that the negative effects outweigh the positives. This article therefore recommends that employee involvement, training, and education on globalisation dynamics are necessary for employees to appreciate emerging issues in the world of work and be equipped to meaningfully engage employers in collective bargaining to improve their plight at the workplace and industry level.